PRINSIP-PRINSIP AL-QUR’AN DALAM PEMBENTUKAN KARAKTER UMAT - Mukhtar Nuhung (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
The Qur'an is the source and human values. As God's clear instructions relating to the human, the message of the Koran bersipat universal, and it was agreed by all Muslims. The problem then is, how to keep the messages of the Koran that uneversal it, especially regarding the development of community characters can be captured and used by everyone at every age. This paper attempts to explore the verses of the Koran to get the outlines of the perisip-perinsip character building in the hope that people can contribute to academic-practice for the reader to be realized in character building among fellow beings in relation to individuals, communities and other nations in the sphere of local, national, regional, and global.